2021
DOI: 10.3390/cryst11111388
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Tensile Mechanical Responses of Selective Laser-Melted Aluminum with Different Crystalline Forms

Abstract: The mechanical deformation of cellular structures in the selective laser melting (SLM) of aluminum was investigated by performing a series of molecular dynamics (MD) simulations of uniaxial tension tests. The effects of crystalline form, temperature, and grain orientation of columnar grains on the mechanical properties of SLM aluminum were examined. The MD results showed that the tensile strength of SLM aluminum with columnar grains at different temperatures was lower than that of single-crystal aluminum, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The stress-strain curves for the samples with GB segregations do not show negative shear stress values because segregations allow a less catastrophic release of the elastic strain energy. Note that negative stress values after critical events associated with sudden structure rearrangement have been observed in many other molecular dynamics simulations [45][46][47].…”
Section: The Effect Of Gb Segregation Of Zr On Shear Deformation Beha...supporting
confidence: 61%
See 2 more Smart Citations
“…The stress-strain curves for the samples with GB segregations do not show negative shear stress values because segregations allow a less catastrophic release of the elastic strain energy. Note that negative stress values after critical events associated with sudden structure rearrangement have been observed in many other molecular dynamics simulations [45][46][47].…”
Section: The Effect Of Gb Segregation Of Zr On Shear Deformation Beha...supporting
confidence: 61%
“…The results for pure Al shown in Figure 3 can be compared with the results of previous molecular dynamics studies. Single-crystal Al shows an ultimate strength from 6 to 8 GPa [46][47][48], depending on the loading scheme and simulation conditions, while polycrystalline samples show much lower strength of about 1 GPa [47,49,50]. In our simulations, parallel GBs are considered, and the ultimate shear stress is about 0.2 GPa.…”
Section: The Effect Of Gb Segregation Of Zr On Shear Deformation Beha...mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting porous samples were subjected to uniaxial tensile stress along the OX axis at the constant rate 1.0 × 10 10 s −1 . It is important to note that such ultra-high strain rates are typical for the molecular dynamics simulation method used to study the process of material destruction under high dynamic loading [66,67]. This rate differs from the experimental strain rate, which can lead to overestimation of mechanical properties in the case of molecular dynamics simulation, for example, as shown in Refs.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…With the development of digital data and machine learning, data-driven modeling has emerged as an effective approach and as a key building block of various AM design and management frameworks, such as design for AM [65], digital twin for AM [66], smart AM [67,68] and cloud AM [69]. Moreover, the molecular dynamic method was used to investigate the effects of crystalline form, temperature, and grain orientation of columnar grains on the mechanical properties of SLM aluminum, which showed that reasonable control of the grain orientation can improve the tensile strength of the AM materials [70]. The Green's function of stresses was used to present the thermal stresses and the Johnson-Cook flow stress model was used to predict the yield surface of the part under repeated heating and cooling [71].…”
Section: Experiments and Numerical Simulationsmentioning
confidence: 99%